The Relationship between Diabetes Self Management and Ankle Brachial Index Value in Patients with Diabetes Mellitus - Fatimah, Okta Milenia; Purwanti, Okti Sri (Indonesian Journal of Global Health Research, 2024)
Diabetes mellitus that is not monitored properly and correctly, it can risk causing various long-term complications that are strongly associated with worsening blood sugar control and can interfere with self-care behavior. Therefore, compliance / discipline is needed from patients in implementing diabetes self-management to improve the quality of life of patients. This study aims to determine the relationship between Diabetes Self Management and Ankle Brachial Index (ABI) values in patients with Diabetes Mellitus at UNS Hospital Surakarta City. The method used in this study is a correlation study with a cross sectional approach, the sampling technique in this study is purposive sampling at UNS Surakarta City Hospital totaling 52 samples from a total population of 106 people. Data analysis of this study was carried out by univariate and bivariate tests and agreement coefficient tests. The correlation results of the Spearman test with a value of 0.326 which shows a fairly strong correlation between the Ankle Brachial Index and Diabetes Self Management with a significant value of 0.018 (0.018 < 0.05) which means it is related or statistically significant.